ALAT UKUR INDUKTANSI DIGITAL BERBASIS ATMEGA 32 - Ramdany, Hanna Fury Nur; Winarno, Heru (Gema Teknologi, 2016)
Hanna Fury Nur Ramdany, Heru Winarno in this paper explain that inductors have an important role in the field of electronics. Many values of capacitors and inductors whose values are difficult to translate, namely when capacitors and inductors are of low value and the color of the print is less clear , also considering the human read factor when an analog measuring instrument is used. From these problems, it is designed an inductance measuring instrument (L Meter) whose results can be directly displayed.The research method used in the manufacture of inductance meter measuring instruments is the literature method and laboratory tests using frequency variables generated or read by the oscillator circuit. The inductance measuring instrument designed in this researc is simple and meticulous measuring instrument that can be read and used by everyone. This digital inductance meter can be used to measure inductance - inductance with a level or a range of measurements between 20μH –100mH.The lower the inductor value measured, the higher the percentage error. So that the tools designed must be able to work well. The average error ratio of an inductance meter with a standard LCR meter is 6.5%. . Keywords: Measuring, Inductor, Microcontroller and LCD DisplayReferencesMimail,B. (2011) Dasar Teknik Elektro Rangkaian Listrik.Malang UB Press.Malvino, A.P. (1979). Prinsip-Prinsip Elektronik Edisi Kedua (terjemahan Hanapi Gunawan). Jakarta:Erlangga.Malvino, A.P. (1996). Prinsip-Prinsip Dasar Elektronika Edisi Ketiga (terjemahan Prof. M. Barmawi, Ph.D. , M.O. Tjia, Ph.D., Departemen Fisika, Institut Teknlogi Bandung). Jakarta: Erlangga.Bishop, O. (2004). Dasar-Dasar Elektronika (terjemahan Irzam Harmein S.T). Jakarta: Erlangga.Yuliana, E. (2006). Rancang Bangun Alat Induktansi dan Kapasitansi Meter. Semarang. Universitas Negeri Semarang.Amallia, F. (2009). Rancang Bangun Kapasitansi dan Induktansi Meter Menggunakan Mikrokontroler Atmega8 Dengan Tampilan LCD. Jakarta. Universitas Mercu Buana.Frank D, Petrezuella. (2001). Elektronika Industri. Yogyakarta: Andi